Characterization of puma-livestock conflicts in rangelands of central Argentina - Guerisoli, Maria de Las Mercedes (2017)
Livestock predation is one of the major causes of conflicts between humans and pumas (Puma concolor). Using data from interviews with ranchers and kill-site inspections, we characterized puma-livestock conflicts in Villarino and Patagones counties of central Argentinean rangelands. Depredation was considered the major cause of livestock losses, and puma attacks were reported in 46.6% and 35.4% of ranches in Villarino and Patagones, respectively. The majority of ranches underwent losses smaller than 1000 USD. The proportion of livestock lost to predation (0.1-10.4%) and financial losses (5.3-1560.4 USD) per ranch/year varied across ranches, and small sheep ranches in Villarino were affected the most. Depredation was recorded only at night and preferentially in grassland with shrubs and cropland habitats. Although nocturnal enclosures appeared to decrease sheep losses, puma hunting was considered the most effective form of reducing depredation and was implemented by most ranchers. Mortality rates were 3.7 and 1.1-1.56 individuals/year × 100 km2 for sheep and pumas, respectively. Nocturnal fencing, shepherding and spatial separation from predators may efficiently reduce sheep losses. However, the poor association between the intensity of puma persecution and puma-related livestock losses suggests that conflict mitigation in central Argentina is not only about reducing damage but also about increasing tolerance